2015
DOI: 10.1007/s10571-015-0220-8
|View full text |Cite
|
Sign up to set email alerts
|

Hairy and Enhancer of Split 6 (Hes6) Deficiency in Mouse Impairs Neuroblast Differentiation in Dentate Gyrus Without Affecting Cell Proliferation and Integration into Mature Neurons

Abstract: Hes6 is a member of the hairy-enhancer of split homolog (Hes) family of transcription factors and interacts with other Hes family genes. During development, Hes genes are expressed in neural stem cells and progenitor cells. However, the role of Hes6 in adult hippocampal neurogenesis remains unclear. We therefore investigated the effects of Hes6 on adult hippocampal neurogenesis, by comparing Hes6 knockout and wild-type mice. To this end, we immunostained for markers of neural stem cells and progenitor cells (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…At 12 weeks of age, the animals ( n = 10 in each group) received an intraperitoneal injection of 5-bromo-2′-deoxyuridine (BrdU; Sigma, St. Louis, MO, USA) at a dosage of 50 mg/kg in saline twice daily for three consecutive days to examine the effects of D-gal and ascorbic acid treatment on the differentiation of BrdU-positive cells into mature neurons in the dentate gyrus [21]. Animals were sacrificed four weeks after the final day of BrdU treatment for histology analysis (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 12 weeks of age, the animals ( n = 10 in each group) received an intraperitoneal injection of 5-bromo-2′-deoxyuridine (BrdU; Sigma, St. Louis, MO, USA) at a dosage of 50 mg/kg in saline twice daily for three consecutive days to examine the effects of D-gal and ascorbic acid treatment on the differentiation of BrdU-positive cells into mature neurons in the dentate gyrus [21]. Animals were sacrificed four weeks after the final day of BrdU treatment for histology analysis (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Double immunofluorescence staining was performed as described in the previous study [21]. DNA denaturation was conducted for BrdU immunostaining.…”
Section: Methodsmentioning
confidence: 99%
“…The oncogenic role of HES6, a helix-loop-helix transcriptional suppressor, has been previously reported in several studies: for example, HES6 was demonstrated to regulate the differentiation of numerous cell types during myogenesis ( 27 ). Nam et al ( 28 ) proposed that HES6 binds to HES1, suppressing the function of HES1 and promoting the differentiation of neural stem cells. Additionally, elevated HES6 expression was reported to lead to a significant increase in the invasive phenotype of prostate cancer and glioma ( 14 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from this research suggested that silencing MIR22HG might enhance gastric cancer cells proliferation, migration and invasion by increasing HES6, HEY1 and nucleus NOTCH2 expression. HES6, a member of the hairy-enhancer of the split homolog family, was found to be involved in multiple tumors [25]. It was reported that elevated HES6 expression of patients with hepatocellular carcinoma exhibited adverse prognosis [26].…”
Section: Discussionmentioning
confidence: 99%